2013
DOI: 10.1002/anie.201305375
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Confirmation of Low Surface Energy in LiCoO2 and Implications for Lithium Battery Electrodes

Abstract: Water adsorption on the surface of LiCoO2 nanoparticles was investigated. As the water coverage increases the adsorption enthalpy decreases reaching the enthalpy of water condensation (−44 kJ mol−1). The experimentally observed average surface energy corresponding to all facets agree well with those reported from DFT calculations. The observed low surface energy is attributed to the surface Co3+ spin transition in nanophase LiCoO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 28 publications
5
24
0
Order By: Relevance
“…The ATR‐FTIR spectra of all samples exhibit the fingerprint of R ‐3 m phase of HT‐LiCoO 2 in the 550–700 cm −1 region, where three characteristic bands centered at 558, 584, and 629 cm −1 are identified (asterisks, Figure B). After grinding of LiCoU, four new bands are observed in the 800–1500 cm −1 range (LiCoU45, circles, Figure B); these bands are typically associated to carbonates (CO 3 2− ) .…”
Section: Resultsmentioning
confidence: 99%
“…The ATR‐FTIR spectra of all samples exhibit the fingerprint of R ‐3 m phase of HT‐LiCoO 2 in the 550–700 cm −1 region, where three characteristic bands centered at 558, 584, and 629 cm −1 are identified (asterisks, Figure B). After grinding of LiCoU, four new bands are observed in the 800–1500 cm −1 range (LiCoU45, circles, Figure B); these bands are typically associated to carbonates (CO 3 2− ) .…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the use of LiCoO 2 has been inevitably limited because its stability can be rapidly deteriorated at potentials higher than 4.2 V . Several research groups have reported that the observed poor cycling performance above 4.2 V is caused by a phase transition from a hexagonal phase to a monoclinic phase, which accompanies a volume change of ≈2.6% along the c ‐axis . Other studies demonstrated that the capacity loss of LiCoO 2 above 4.2 V is mainly due to an increase in interfacial impedance between the surface film of the cathode and electrolyte, arising from side reactions involving LiPF 6 ‐based electrolytes and surface impurities generated by air or moisture exposure .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However,t he currently available LIBs are incapable of meeting the changing demands. The technical obstacles are mainly attributed to the limited electrochemical properties of cathode materials, [5] such as low capacity (layered LiCoO 2 ), [6,7] structural vulnerability (spinel LiMn 2 O 4 ), [8,9] and poor conductivity of electron/lithium-ion diffusivity (olivine LiFePO 4 ). [10,11] Among all the cathodem aterials reported so far,l ithium-rich layered oxide materials[ xLi 2 MnO 3 ·(1-x)LiMO 2 ], as as olid solution between layers of Li 2 MnO 3 and LiMO 2 (M = Mn, Ni, Co, and so forth, 0 < x < 1), are recognizedasone of the most promising candidates, because of their low cost and low toxicity,a nd characteristic high specificc apacities ( % 250 mAh g À1 )w hen charged to ah igh upperc utoff voltage (> 4.5 V).…”
Section: Introductionmentioning
confidence: 99%